From the nurse's mouth: the Fezile Dabi ART assessment site experience - Du Plooy, Shirley (University of the Free State, 2006)
HIV/AIDS, together with the implementation of a public sector antiretroviral treatment (ART) programme and the transformation of the health system, places unprecedented pressure on facilities with insufficient nursing personnel. Based on information gathered from group interviews, this paper presents the experience of nurses working at ART assessment sites in Fezile Dabi. Empirical data represent the following domains: perceptions and experiences surrounding the impact of ART, general and staffing needs, training, patient drug-readiness training, the value of volunteers, support and supervision from ART programme managers, and emotional support for and coping mechanisms of staff. Recommendations take account of floor-space, management, additional staff, confidentiality, practical training, drug-readiness training, and coping strategies.

MIV/VIGS, tesame met die implementering van ’n openbare sektor-antiretrovirale terapieprogram (ART), en die transformasie van die gesondheidsisteem plaas onge- kende druk op fasiliteite met beperkte verpleegpersoneel. Gebaseer op data uit groeps- onderhoude, het hierdie artikel ten doel om die ervaring van professionele verpleeg- personeel by ART assesseringsfasiliteite in Fezile Dabi te ondersoek. Die empiriese data dek die volgende areas: persepsies en ervaring rondom die impak van ART, algemene en personeelbehoeftes, opleiding, pasiënt-medikasiegereedheidsopleiding, die waarde van vrywilligers, ondersteuning en toesighouding deur ART-programbestuurders, asook emosionele ondersteuning aan en hanteringsmeganismes van die personeel. Aanbeve- lings hou rekening met die volgende: vloerruimte, bestuur, addisionele personeel, vertrou- likheid, praktiese opleiding, medikasiegereedheidsopleiding en hanteringstrategieë.
Keywords: Antiretroviral treatment (ART); Nursing; Assessment; HIV and AIDS